Changes in the gut microbiota structure and function in rats with doxorubicin-induced heart failure - Fan, Yawen; Liang, Lichang; Tang, Xinzheng; Zhu, Jinxian; Mu, Lei; Wang, Mengni; Huang, Xuecheng; Gong, Shenglan; Xu, Jinghan; Liu, Tianjiao; Zhang, Tianfeng (Frontiers in Cellular and Infection Microbiology, 2023)
Objectives The rat model of heart failure (HF) induced by doxorubicin (DOX), a broad spectrum and highly effective chemotherapeutic anthracycline with high-affinity to myocardial tissue that causes severe dose-dependent irreversible cardiotoxicity has been widely recognized and applied in HF pathogenesis and drug therapy studies. The gut microbiota (GM) has attracted significant attention due to its potential role in HF, and research in this area may provide beneficial therapeutic strategies for HF. Considering the differences in the route, mode, and total cumulative dose of DOX administration used to establish HF models, the optimal scheme for studying the correlation between GM and HF pathogenesis remains to be determined. Therefore, focusing on establishing the optimal scheme, we evaluated the correlation between GM composition/function and DOX-induced cardiotoxicity (DIC). Methods Three schemes were investigated: DOX (at total cumulative doses of 12, 15 or 18 mg/kg using a fixed or alternating dose via a tail vein or intraperitoneal injection) was administered to Sprague Dawley (SD) for six consecutive weeks. The M-mode echocardiograms performed cardiac function evaluation. Pathological changes in the intestine were observed by H&E staining and in the heart by Masson staining. The serum levels of N-terminal pre-B-type natriuretic peptide (NT-proBNP) and cardiac troponin I (cTnI) were measured by ELISA. The GM was analysed by 16S rRNA gene sequencing. Key findings Strikingly, based on the severity of cardiac dysfunction, there were marked differences in the abundance and grouping of GM under different schemes. The HF model established by tail vein injection of DOX (18 mg/kg, alternating doses) was more stable; moreover, the degree of myocardial injury and microbial composition were more consistent with the clinical manifestations of HF. Conclusions The model of HF established by tail vein injection of doxorubicin, administered at 4mg/kg body weight (2mL/kg) at weeks 1, 3 and 5, and at 2mg/kg body weight (1mL/kg) at weeks 2, 4 and 6, with a cumulative total dose of 18mg/kg, is a better protocol to study the correlation between HF and GM.